2020
DOI: 10.3390/foods9101437
|View full text |Cite
|
Sign up to set email alerts
|

Application of Non-Destructive Rapid Determination of Piperine in Piper nigrum L. (Black Pepper) Using NIR and Multivariate Statistical Analysis: A Promising Quality Control Tool

Abstract: Piperine is a bioactive alkaloid compound which provides a unique spicy flavor derived from plants of the Piper nigrum L. Black pepper (n = 160) collected from Vietnam was studied using non-destructive near infrared spectroscopy (NIRS). The spectral acquisition ranged from 1100 to 2500 nm, and a chemometrics analysis program was performed to quantify the piperine contents. High performance liquid chromatography (HPLC) analysis was carried out to develop a chemometric model based on reference values. The black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…In addition to piperine, many other amides have been isolated from the Piper species [13,14]. Studies on the pharmacological effects of piperine have shown that it has antimicrobial, anticancer, anti-inflammatory, insecticidal, analgesic, anticonvulsant, antiulcerogenic, gastroprotective, antioxidant, and antiseptic properties; piperine also makes other bioactive compounds more absorbable and bioavailable [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to piperine, many other amides have been isolated from the Piper species [13,14]. Studies on the pharmacological effects of piperine have shown that it has antimicrobial, anticancer, anti-inflammatory, insecticidal, analgesic, anticonvulsant, antiulcerogenic, gastroprotective, antioxidant, and antiseptic properties; piperine also makes other bioactive compounds more absorbable and bioavailable [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…(1) where: C = Piperine concentration in the sample (g/100 mL) read from the standard curve W = Sample weight V = Volume of Erlenmeyer tube (ml) Fp = Dilution factor Raman spectroscopy [42] or near-infrared spectroscopy [43] wether it is used as benchtop or handheld spectrometers [44] may also be used as a rapid estimation of piperine in black pepper. On the other hand, the utilization of Reverse Phase High-Performance Liquid Chromatography approach leads to the development of a more precise and reliable method [45].…”
Section: Non-conventional Methodsmentioning
confidence: 99%
“…Metode NIRS dipilih karena berpotensi besar untuk diterapkan dalam memprediksi secara cepat dan akurat sehingga dapat menjadi suatu sistem evaluasi kualitas pada produk pertanian. Penelitian tentang penerapan NIR Spectrometer untuk penentuan kandungan kimia produk pertanian telah banyak dilakukan, misalnya penentuan kadar piperin lada putih (Athfiyah et al, 2020), serta hal yang sama untuk lada hitam (Park et al, 2020), namun penggunaan NIR Spectrometer secara spesifik terhadap bubuk lada hitam masih perlu penelitian lebih mendalam. Tujuan dari penelitian ini adalah untuk menganalisis metode pengukuran kadar air dan kandungan piperine pada lada hitam dengan menggunakan metode NIRS dengan penerapan metode PLS (Partial Least Square) dan PCR (Principal Component Regression).…”
Section: Pendahuluanunclassified